(3JNejS GdHQOIs - (3CHi YHO Gddg eMeO GdeQGcTis; (3GdHhUjQj,J (B696 (3g` s
(3ChdgG (B:s
(3JNejS GdOQjI GdSfjI ai eOM NjQ GdHQjI bGd(B: (3eGHGd Yjfjc JTch TOI GdCde QeOGA fGeJ Yjhf hgj de Jfe JPQi OeG hOehYG ai QLi GdXde Cef JPcQ LjQGf HPi Sde s
(3BNQgG (B:s
(3JVMc GdRgQ MjGg GdMjG aNHG WjH GdTeje aCHOi efXQG YLHG LQi GdTPG hGdfOi ai TYQg TfHG eGQfMJ YPHGJ GdHGf QjM UHG hCWQH GdYjS MGOi GdYjS HGdfZe s
(3Vef eLehY , JQJjHgG (B: 12s
(3GfXQgG eY HgLI GdLGdS hCfS GdeLGdSs
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3JNejS TYQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
Keywords: (3GdCOHs